Two teachers learn from their students: Examining teaching, learning, and the use of learning centers - Barbara Dian O'Donnell; Rebecca Hitpas (Networks: An Online Journal for Teacher Research, 2010)
Two teachers, a kindergarten teacher and university professor, used action research to study the use of learning centers in their respective classrooms. Becky, a kindergarten teacher, collected and analyzed qualitative data in the form of interviews, work samples, anecdotal records, checklists, videotapes, and culminating performance task documents. She found that at-risk students made progress in achievement, accountability, and motivation. Inspired by Becky’s study, her university advisor/teacher redesigned a learning center assignment that proved to be more powerful in getting teacher candidates to understand, design, and use centers.